KEPASTIAN HUKUM PERMOHONAN PEMBATALAN PERKAWINAN YANG DALUWARSA MENURUT UNDANG-UNDANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM - Nurmah; Wira Fransisca; Nur Hakim (Journal of Innovation Research and Knowledge, 2025)
Article 72 paragraph (3) of the Compilation of Islamic Law and Article 27 paragraph (3) of Law No. 1 of 1974 on Marriage explicitly state that the maximum time limit for filing a marriage annulment is 6 months. However, in practice, judges often still grant annulment requests even after the 6-month period has passed, leading to legal uncertainty.The method used in this research is a juridical-normative type of research, which is legal research based on literature or secondary data, utilizing sources from primary, secondary, and tertiary legal materials. The research approaches used in this thesis include the conceptual approach, the statutory approach, the case approach, and the analytical approach.Research Findings on the Legal Consequences of a Marriage Annulment Petition Filed After the Expiration Period The judge's decision to grant the annulment of the marriage, despite the petition being filed after the statutory time limit, indicates that the statute of limitations in filing for marriage annulment is not considered an absolute requirement. In deciding the case, the judge prioritized the validity of the marriage, particularly the existence of a marriage prohibition that rendered the marriage null and void by law (null and void ab initio). Legal certainty regarding marriage becomes compromised when a court annuls a marriage in contradiction to Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law. The annulment of a marriage by the court based on grounds that conflict with the applicable law undermines the principle of legal certainty. In such cases, the petition for annulment that has exceeded the time limit should have been rejected, and alternative legal remedies, such as filing for divorce, should be pursued instead.